Inventory of temporalities (cartographic notes) (Revista Apotheke, 2022)
Traces of poetic-educative presences, cartographed along my research path as an artist-walker-teacher in a transition period from Recife-PE (where I worked as a substitute teacher of the Visual Arts course at UFPE, between 2017 and 2018) to South of Bahia (where I work as an effective professor at UFSB, since 2019), passing through the Midwest (where I was born). A composition that I have been doing in Campinas-SP (where I carry out my Doctoral research in Education at UNICAMP, since 2021). Inventory (listed and invented) of times, rather than verbal, situational. Notes written in singular contexts, which carry seeds of the plurality of other experiences that can arise from the community of readers who find them around/here. Under experimenting with ways to share academic research processes and beyond. From the theses we wrote yesterday from what will be lived tomorrow, with the words of today.
Keywords: temporality; presence; route; poetical-cartographic writing; research